Electrochemical detection of lead and cadmium in UHT-processed milk using bismuth nanoparticles/Nafion®-modified pencil graphite electrode - Palisoc, Shirley T. (Animo Repository, 2019)
Pencil graphite electrodes (PGEs) were modified with bismuth nanoparticles and Nafion® using the drop-coating method. Simultaneous detection of trace cadmium (Cd 2+ ) and lead (Pb 2+ ) in ultrahigh-temperature-processed milk samples were done via anodic stripping voltammetry using the modified PGE as the working electrode. Scanning electron microscopy and energy-dispersive x-ray analyses were conducted for the morphological characterization of the modified PGE. The limit of detection was found to be 7.31 μg/L for Cd 2+ and 31.07 μg/L for Pb 2+. Trace quantities of Cd 2+ and Pb 2+ in the milk samples were detected. Results showed that all milk samples have tolerable daily intake less than the World Health Organization's permissible daily consumption of trace heavy metals of 0.83 μg/kg bw based on the average adult body weight (60 kg) and estimated volume of daily milk consumption (0.5 L). © 2019 The Authors